Combined treatment approach with citicoline and thrombolytics in cerebrovascular stroke - Varahabhatla Vamsi; Sikorska, Marina; Сікорська, Марина Володимирівна (Polish Academy of Sciences, 2018)
Thrombolytic therapy (TLT) for today is the only evidence-based method for stroke treatment. In cerebral ischemia, the disintegration of phosphatidylcholine occurs with the release of free fatty acids. Citicoline in acute stroke reduces damage to the integrity of membranes and reduces the production of free radicals. Aim. The aim of this work is to analyse the treatment outcome with and without Citicoline as a combination therapy to TLT in patients with ischemic stroke.